인공강수가 하천수의 부영양화 물질 농도변화에 미치는 영향평가 - 정은실 (한국수처리학회지, 33(3), 2025)
This study investigates the potential environmental impacts of wintertime artificial precipitation experiments on stream water quality by analyzing long-term monitoring data from the Odaecheon-1 site, located downstream of a site where ground-based cloud seeding has been conducted annually in the mountainous region of Daegwallyeong, South Korea. From 1997 to 2023, water quality data were collected and evaluated with a focus on March (the thawing period immediately after winter seeding operations) and October (a non-seeding control period). Key parameters analyzed include total nitrogen (TN), total phosphorus (TP), chlorophyll-a (Chl-a), electrical conductivity (EC), dissolved oxygen (DO), water temperature, and pH. Linear regression and correlation analyses revealed statistically significant increases in EC and water temperature, and a notable decrease in DO during March, suggesting seasonal physical changes potentially linked to cloud seeding activities. While TN and TP concentrations remained largely stable, Chl-a levels in March exhibited a gradual upward trend, indicating possible biological responses. Strong positive correlations between EC and TN, and moderate correlations between EC, DO, and Chl-a, further support the hypothesis that physical conditions altered by cloud seeding may influence algal productivity indirectly. October data showed minimal trends or correlations, affirming its role as a suitable control period. These findings suggest that wintertime cloud seeding may lead to subtle but measurable changes in downstream water quality, particularly through indirect effects on biological indicators such as Chl-a. This study highlights the importance of long-term, seasonal monitoring for assessing the environmental safety of weather modification technologies and provides a scientific basis for future sustainable water resource management. KCI Citation Count: 0